2008
DOI: 10.1021/jf800225y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ethanol, Temperature, and Gas Flow Rate on Volatile Release from Aqueous Solutions under Dynamic Headspace Dilution Conditions

Abstract: On the basis of a mechanistic model, the overall and liquid mass transfer coefficients of aroma compounds were estimated during aroma release when an inert gas diluted the static headspace over simple ethanol/water solutions (ethanol concentration = 120 mL x L(-1)). Studied for a range of 17 compounds, they were both increased in the ethanol/water solution compared to the water solution, showing a better mass transfer due to the presence of ethanol, additively to partition coefficient variation. Thermal imagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
54
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 22 publications
7
54
0
Order By: Relevance
“…Both black and white areas combine to give AreaTotal. fected CO 2 evolution 11 and volatile partitioning 19 11 , which may result in a reduced quantity of volatiles being carried away with the escaping gas. In addition, with direct sampling techniques such as APCI-MS and proton transfer reaction-mass spectrometry (PTR-MS), the headspace is often diluted by air as the sample is drawn into the MS.…”
Section: Headspace Sampling -Staticmentioning
confidence: 99%
“…Both black and white areas combine to give AreaTotal. fected CO 2 evolution 11 and volatile partitioning 19 11 , which may result in a reduced quantity of volatiles being carried away with the escaping gas. In addition, with direct sampling techniques such as APCI-MS and proton transfer reaction-mass spectrometry (PTR-MS), the headspace is often diluted by air as the sample is drawn into the MS.…”
Section: Headspace Sampling -Staticmentioning
confidence: 99%
“…It was indeed recently demonstrated that the continuous flow of ascending bubbles strongly modifies the mixing and convection conditions of the liquid medium [7][8][9][10]. In turn, the CO 2 discharge by diffusion through the free air/champagne interface may be considerably accelerated, as well as the release of the numerous VOC, which both strongly depend on the mixing flow conditions of the liquid medium [11]. Suffice to say that a strong coupling therefore finally exists between rising bubbles, glass shape, CO 2 discharge and flavor release.…”
Section: Introductionmentioning
confidence: 99%
“…With this modification in place, the release of aroma from ethanolic solutions was studied using the dynamic headspace dilution technique. This showed that, although ethanol tended to reduce the gas-phase aroma concentration at equilibrium due to a changed partition value, the concentration in the gas phase during dynamic headspace dilution was greater for some compounds than for the corresponding water control (Tsachaki et al, 2005;Tsachaki et al, 2008). This behaviour can be attributed to the Marangoni effect, a sequence of events that starts with ethanol evaporation from the air-liquid interface.…”
Section: Measuring Aroma Release In Ethanolic Beveragesmentioning
confidence: 98%
“…This behaviour can be attributed to the Marangoni effect, a sequence of events that starts with ethanol evaporation from the air-liquid interface. This causes changes in interfacial tension, which sets up convection currents in the bulk phase and effectively stirs the bulk phase, therefore avoiding aroma concentration gradients in the liquid phase (Tsachaki et al, 2008). By developing this analysis, the dynamics of aroma release from ethanolic solutions were determined.…”
Section: Measuring Aroma Release In Ethanolic Beveragesmentioning
confidence: 99%